A prospective study comparing tryptophan immunoadsorption with therapeutic plasma exchange for the treatment of chronic inflammatory demyelinating polyneuropathy*. Issue 6 (9th May 2017) - Lieker, Ina; Slowinski, Torsten; Harms, Lutz; Hahn, Katrin; Klehmet, Juliane
Abstract: Background: Chronic inflammatory demyelinating polyneuropathy (CIDP) is a rare paralyzing inflammatory neuropathy with probably autoimmune origin. While plasma exchange (PE) constitutes a first‐line treatment option for CIDP, there is only little known about the efficacy and safety of immunoadsorption (IA), a more selective apheresis procedure with assumed better tolerability. Methods: In this prospective‐randomized pilot trial, patients were randomly assigned to receive 6 sessions of PE ( n = 10) or IA ( n = 10) treating equal plasma volumes. To evaluate efficacy, we calculated the adjusted Inflammatory Neuropathy Cause and Treatment (INCAT) disability score and the Medical Research Council (MRC) sum score at baseline (V1), after completion of 6 sessions (V2) as well as 4 weeks after completion (V3) in 9 patients per group (1 patient in each group did not complete follow‐up). We additionally assessed safety and tolerability of treatments by monitoring adverse event and blood parameters. Results: With IA, 6 out of 9 (66.7%) patients improved clinically, whereas with PE, 4 out of 9 (44.4%) patients improved, most of them immediately with completion of the apheresis treatment series. There was one adverse event (AE) out of 52 treatment sessions for the 9 patients in the IA group. In the PE group of 9 patients, there was 1 AE out of 51 sessions and a trend of greater fibrinogen reduction. No severe AE occurred in either group. Conclusion: The results of this pilot study suggest that IA is at least equally effective and safe compared to PE in CIDP patients.